SYNTHESIS OF CRACKING CATALYST FOR VGO AND PALM OIL - Budiyanto
Indonesia has depleted petroleum reserves and unable to meet national demand but rich in vegetable oil resources, especially palm oil. Palm oil can be used as a substitute and a mixture of petroleum in several processes in the refinery, including cracking units. Cracking unit is used to crack the feed into smaller molecules, where gasoline is the main product. Cracking unit can contribute almost 50% of gasoline production in the refinery. This potential makes it possible to transfer technology from a nonrenewable resource base to a renewable resource-based technology. Two types of cracking catalysts developed in this study, each for VGO and palm oil. VGO cracking catalysts have long been known and are generally composed of zeolites, matrices, fillers, and binders. In some cases, additives are also added to increase or suppress certain products. Important parameters that are known in the VGO cracking catalyst are used as a reference in the development of the VGO cracking catalyst and palm oil cracking catalyst. Zeolite Y and ZSM-5 with specific characteristics successfully synthesized at the earliner of the study. Zeolite Y and ZSM-5 synthesized had SiO2/Al2O3 ratio 4,5 and 30. The seed and Na2O in the zeolite Y mixture were observed to be very important in helping direct the formation of zeolite crystals and the ratio of SiO2/Al2O3. Synthesis of zeolite Y without the use of seeds in the composition and conditions observed in this study failed to provide a crystal structure. ZSM-5 was synthesis using SDA and in this study is not observed about important process parameters therein. Zeolites are silica-alumina crystals and have very small pores, zeolites Y 7.4 A and ZSM-5 5.5 A. The Zeolite pore to small compare to the feed, making it difficult for molecular diffusion to access the inner surface of zeolite. This diffusion barrier becomes the limiting step in the cracking reaction. Zeolites which have mesoporous channels were developed to reduce these diffusion barriers and are commonly referred to as hierarchical zeolites because they have microporous and mesoporous channels. Hierarchically zeolites in this study developed by the post-synthesis method, by additional treatments after zeolites were successfully synthesized. Additional treatments performed on zeolite Y differed from treatment on ZSM-5 based on the ratio of SiO2/Al2O3. Zeolite Y are consecutively treated with dealumination-desilication-dealumination treatment, this treatment is intended to form a large pore size and increasingly conical to the inside of the zeolite. This treatment succeeded in increasing catalyst activity significantly, as seen from gasoline yields which could be increased from 22.68% when using conventional zeolite Y to 55.97% with the use of hierarchical zeolite Y. Hierarchical ZSM-5 synthesized by several methods, desilication with strong bases and desilication with weak bases combined with dealumination. This procedure succeed to increase gasoline yield compared to the use of conventional ZSM-5, which is 34.34% compared to 60.86%. Cracking catalyst was developed using zeolite Y and ZSM-5 synthesized. Zeolites, matrices, fillers (kaolin), and binders (sol-silica) are varied to obtain the catalyst formula with the highest gasoline yield. The VGO cracking and the palm oil cracking, has the same Z/M synergy profile for conversion and product yield, in means, this parameter can apply generally. Z/M synergy is directly proportional to the gasoline acquisition profile. Al2O3 levels in the matrix also provide relatively identical profiles for the two types of cracking catalysts observed. Gasoline yields tend to be higher when lower Al2O3 matrices are used. The use of hierarchical zeolites can increase catalyst activity, especially in VGO cracking. However, the use of the zeolite hierarchy in cracking palm oil did not succeed in providing better activity than the Z / M composite. The highest gasoline product in cracking of VGO obtained by formula: zeolite Y / matrix / kaolin / binder hierarchy = 29.6 / 7.4 / 43/20 (% weight). Whereas in the cracking of palm oil, the highest gasoline (53%) obtained with the catalyst formula: ZSM5 / matrix / kaolin / binder = 45.6 / 11.4 / 23/20 (each in% by weight). The palm oil cracking catalyst obtained was further studied by the reaction kinetics using three kinetic models (3-lump, 4-lump, and 5-lump). Based on the study it found that the rate of cracking of palm oil runs in 2nd order and cracking gasoline runs in 1st order of reaction. The reaction kinetic of 3-lump and 4-lump models gives better results than the 5-lump model.